Psychological Factors Influencing Basic Badminton Skills Acquisition in Junior Players: A Path Analysis Study - Sandika Fauzi; Arief Rahman Azizy Ritonga; Egi Hagata (Joska: Jurnal Isori Kampar, 2025)
Objectives: The development of junior badminton players hinges on fundamental skill acquisition. Although the physical and technical dimensions are extensively researched, the psychological factors affecting young athletes in badminton remain underexplored. This research examined the interconnections among sport confidence, intrinsic motivation, cognitive anxiety, and skill acquisition in junior badminton players. Methods: Thirty male junior badminton players participated in a 12-week study. Psychological factors were evaluated using various established inventories. Skill acquisition was quantified through a specialized Badminton Skill Test Battery. Path analysis was utilized to investigate the relationships between psychological factors and skill acquisition. Results: The path analysis model demonstrated excellent fit indices (CFI = .99, TLI = .98, RMSEA = .032, SRMR = .031). Sport confidence exerted the most substantial direct impact on skill acquisition (β = .42, p < .01), succeeded by intrinsic motivation (β = .35, p < .01). Cognitive anxiety adversely affected skill acquisition both directly (β = -.28, p < .05) and indirectly via sport confidence (β = -.15, p < .05). Intrinsic motivation also exhibited an indirect influence through sport confidence (β = .18, p < .05). The model accounted for 53% of the variance in skill acquisition. Conclusion: Sport confidence is identified as the primary determinant, indicating that enhancing confidence should be prioritized in youth badminton training initiatives. The beneficial effects of intrinsic motivation highlight the necessity of promoting enjoyment and personal engagement in the sport. The adverse effects of cognitive anxiety underscore the imperative for the integration of anxiety management strategies in the development of junior players.